Characterization of the Root Nodule Microbiome of the Exotic Tree Falcataria falcata (Fabaceae) in Guangdong, Southern China - Siyu Xiang; Shu Yan; Qianxi Lin; Rong Huang; Runhui Wang; Ruping Wei; Guandi Wu; Huiquan Zheng (Diversity, 2023)
Falcataria falcata is an exotic tree species that was imported to southern China around 1940 and has been widely planted in the Guangdong province of China. Using the 16S rRNA amplicon sequencing approach, we investigated the composition of the bacterial endophytes in the root nodules of naturally grown F. falcata and elucidated the core bacterial endophyte group. Across all samples, there were 575 bacterial genera and 29 bacterial phyla. Proteobacteria accounted for 42–90% relative abundance in all regions. Notably, Bradyrhizobium, Paucibacter, Rhizobium, and Mesorhizobium were consistently detected in all regions studied. Among these, Bradyrhizobium (13–37%) and Paucibacter (1–34%) were the dominant genera. Despite the differences in endophytic amplicon sequence variants (ASVs) across all regions, our results demonstrate that some ASVs, which have been termed herein as commonly shared core ASVs (c-ASVs), still inhabit F. falcata root nodules across multiple regions simultaneously. More importantly, some c-ASVs dominated in F. falcata root nodules across multiple regions. This study demonstrated the consistency of the bacterial endophyte communities of F. falcata root nodules.